High-sensitivity human papilloma virus genotyping reveals near universal positivity in anal squamous cell carcinoma: Different implications for vaccine prevention and prognosis. Issue 6 (April 2015) - Baricevic, Ivona; He, Xiaotong; Chakrabarty, Bipasha; Oliver, Anthony W.; Bailey, Charles; Summers, Jeff; Hampson, Lynne; Hampson, Ian; Gilbert, Duncan C.; Renehan, Andrew G.
Abstract Background Characterisation of human papilloma virus (HPV) infection in anal squamous cell carcinoma (ASCC) may have dual importance: first, aetiological; second, prognostic, informing outcome after chemo-radiotherapy (CRT). We undertook HPV genotyping, and allelic characterisations, to evaluate the aetiological role of HPV while simultaneously evaluating the impact of HPV genotyping on relapse-free (RFS) and overall survival (OS). Method Dual-primer HPV genotyping (subtypes 6, 11, 16, 18, 31, 33, 45, 52, 58) and DNA sequencing of HPV 16 positive tumours were analysed in 151 consecutively referred ASCCs, previously characterised by immunohistochemistry for p16 expression. In 110 patients treated with CRT, factors influencing RFS and OS were evaluated using univariate and multivariate models. Results HPV positivity was observed in 95%. HPV 16 accounted for 89%; of these, 64% harboured the T350G E6 variant. HPV 16 positivity was significantly correlated with improved 5-year RFS (62% versus 40%; p = 0.027) and OS (59% versus 38%; p = 0.019). p16 expression was also significantly correlated with improved 5-year RFS (positive versus negative: 65% versus 16%; p < 0.0001) and OS (63% versus 13%; p < 0.0001). In multivariable models that included HPV 16 status, p16 status, sex, and age, p16 expression remained an independent prognostic factor for RFS (p < 0.0001) and OS (p = 0.002). Conclusion In ASCC, near-universal HPV detection rates were demonstrated, higher than generally reported in the literature, and supporting the development of multivalent HPV vaccinations for prevention. By contrast, p16 negatively, but not HPV 16 genotype, is an independent adverse prognosticator after chemo-radiotherapy in patients with ASCC.